Projeto, montagem e teste de um subwoofer ativo - Silva, Wellngton Corrêa de Faria (Universidade Federal de São Carlos, 2023)
The present work describes in detail the development and construction of an active bass reproduction system "subwoofer". For this, it uses a TPA3255 integrated circuit. This class D amplifier has two outputs that are applied to each of the two 4 Ω coils of the BRAVOX-P12X-D4 loudspeaker, which has a nominal power of 220 WRMS. In addition, the system has adjustment features (volume control, phase inversion and adjustable low-pass filter) and protection (against overvoltage, overcurrent and filters). All circuits were mounted on printed circuit boards and their operation was evaluated through performance measurements. A comparison of the costs involved in the project in relation to the commercialized models was also carried out.
Design, build and test of an active subwoofer
Keywords: Class D Amplifier TPA3255; Low-pass adjustable; Active subwoofer; Amplificador Classe D TPA3255; Filtro passa-baixas ajustável; Subwoofer Ativo; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS